Прогнозування ризиків виробничого травматизму на підприємствах харчової промисловості - Євтушенко, Ольга Володимирівна (НУХТ, 2013)
У статті розглянуто та проаналізовано існуючі методи прогнозування ризику виробничого травматизму. Для прогнозування виробничого травматизму у роботі використано метод головних компонент, завдяки основним властивостям якого забезпечується мінімальна похибка прогнозу. The article consists of analyzed methods revive, which are used for the forecasting of occupational injury risk. Results of the forecast methods analysis show their inability for processing of different statistical data with significant errors. One of perspective scientific directions for increasing of general production safety is the injury risk forecasting, which connected with production process. The analysis of these forecasting methods allows to draw a conclusion about necessity of their improving with aim to assign all complex of injury risks at an enterprise. In this work, general model of injury risk is improved, and it – instead of other models - accounts all specter of production and social-economic factors, and it’s based on scheme of accident appearance. This approach allows to analyze direct cause-and-effect connections, which take a part in injury process. It is indentify main and latent reasons of occupational injury, and also, sorts of events, which cause an accident, by the data of annual reports.
Keywords: безпека; праця; травматизм; ризик; нещасний випадок; прогноз; safety; work injuries; risk; accident; кафедра екології та екоменеджменту